Intussusception due to caecal carcinoma in a young man: unusual cause of presentation a case report - Gujar, Ajay Ashok; Ambardekar, Ravindra S.; Rane, Nikhil; Sharma, Yashsvi; Ali, Sheena; Karpe, Makarand (International Journal of Research in Medical Sciences, 2017)
A young 26 year male patient admitted with colicky pain in right iliac fossa with well palpable tender lump. After radiological investigation lump was diagnosed as ileocaecal intussusception. Patient underwent laparoscopy which diagnosed as intussusception due to caecal carcinoma. Laparoscopy again proved to be useful diagnostic tool over imaging techniques in this case. Laparoscopic assisted surgery of right radical hemicolectomy done successfully.